Development of Patane and Its Impact on the Environment in Toraja - Yulius Pakiding; Alexander Pakiding; Harmelia Tulak; Adel Rante Payung (Edumaspul: Jurnal Pendidikan, 2024)
The cemetery as a place to store the body is a very important place for the Toraja community. In the past, the most widely used places as graves were in specially made stone burrows, in natural stone caves that were considered safe, in certain woods usually for the corpses of babies and partly buried in the ground. In modern times, many Toraja people choose to build a special place for burials called Patane with various considerations. Usually this place was built by one family and became a family cemetery. The size varies according to the wishes of the family concerned but on average is 4 x 6 m with a height of about 3 m. The location of the patane construction depends on the family's agreement and usually uses a place that is considered strategic or good. From the results of the research carried out, the growth of patane buildings is an average of two patane buildings built every year with an average building area of 33.63 m2 and using an average land area of 100.9 m2. The environmental impacts caused are: 1. Positive impacts, namely the location of a neat and well-organized patane building can become a tourist attraction and Because each patane building can accommodate many bodies, it can save land use for the cemetery (if all the bodies stored in the patane are buried in the ground). 2. Negative impact, namely the arrangement of the environment is not neat because the location of the patane development is not well organized because there are no rules about its construction and the reduction of productive strategic space of around 100.9 m2 every year. (compared to using stone burrows, erongs, and caves that use unproductive land).